Modification of path-finding algorithms introducing time and distance limitations - Wolanin, Mateusz; Korniszuk, Klaudia; Smołka, Jakub (Journal of Computer Sciences Institute, 2019)
This paper describes modifications of path-finding algorithms. The modifications add time and distance constraints to generated paths. A* and BFS algorithms are modified. Additionally, A* algorithm modification which combines the advantages (generating the shortest routes with the smallest number of vertices) of A* and BFS is presented.. This allows for creating a route planning app that enables users of bike sharing services to travel more easily and economically.